Olhares cruzados sobre ser jovem e estudante do ensino médio: contextos, experiências e reflexões - Angélica Silvana Pereira; Rosemeire Reis (EccoS – Revista Científica)
The objective of this paper is to bring to light the results of a quantiqualitative research that analyzed the future plans, as well as school and studying senses for high school young students from a public school in Maceió (AL). This text focuses on life contexts of these students, connections, and disparities between youth sociability practices and school life. We intend to discuss about this supposed dichotomy between life inside and outside school, in order to potentiate a debate about their identities as young subjects and high school students, favoring multiple comprehensions about them. This analysis is believed to favor the emergence of questions regarding high school arrangements and practices, in which youth demands and desires are produced and that, in general, seem to weave little interlocutions with today’s young students.